Smart graphics : 13th International Symposium, SG 2015, Chengdu, China, August 26-28, 2015, Revised selected papers /: 13th International Symposium, SG 2015, Chengdu, China, August 26-28, 2015, Revised selected papers. (2017) - Unknown
No abstract available